The Influence of Overconfidence Bias on Stock Investment Decisions - Erie Irianti; Said Kelana Asnawi; Ramdany Ramdany (Community Engagement and Emergence Journal (CEEJ), 2026)
This study concludes that stock trading activity, stock investment risk, and stock diversification have positive effects on stock investment decisions. First, stock trading activity positively influences stock investment decisions, indicating that the higher the intensity of trading activities carried out by investors, the greater their tendency to make stock investment decisions. This phenomenon reflects investors’ active involvement in the capital market, driven by overconfidence bias and the ease of access to information through digital platforms such as Stockbit. However, the magnitude of this influence is relatively small, suggesting that the increase in investment decisions reflects the quantity rather than the quality of decisions. Second, stock investment risk has a positive influence and is identified as the most dominant factor affecting stock investment decisions. This finding indicates that investors’ awareness of risk encourages them to conduct more in-depth evaluations before investing. Risk is no longer perceived as a barrier, but rather as a driver of more cautious, rational, and well-planned investment decision-making. Third, stock diversification positively affects stock investment decisions. Investors who are more rational and well-educated tend to understand the importance of portfolio risk diversification, making them more confident and strategic in making investment decisions. Overall, the findings indicate that stock trading activity, stock investment risk, and stock diversification simultaneously have positive effects on stock investment decisions, with stock investment risk being the most dominant factor. These findings support heuristic theory, which states that investors rely on practical rules and self-confidence in decision-making. However, in the context of modern investors using digital platforms such as Stockbit, investment behavior tends to be more rational and analysis-based.